Meningkatkan Keterampilan Menanam Bawang Prei Melalui Metode Project Based Learning bagi Anak Hambatan Penglihatan Kelas IX - Wahyuni, Sri; Sopandi, Asep Ahmad (Universitas Negeri Padang, 2023)
This study highlights the difficulty of teaching children with visual impairments in class IX at SLB N 1 Padang Panjang how to properly plant leeks because there isn't enough engaging education for them. As a result, the issues that will be investigated in this study include how visually impaired children at SLB N 1 Padang Panjang learn to plant leeks and whether or not this project-based learning approach is effective in enhancing their abilities to do so. Classroom action research is the method used in this study, and it consists of a single cycle divided into multiple stages: preparing, carrying out, observing, and pondering Observation and tests are used to collect the data. Quantitative and qualitative data analysis are used. The findings demonstrated that the Project Based Learning approach to teaching visually impaired children the skills of leek planting was highly effective. After receiving an action, children's learning outcomes demonstrate a positive improvement. Ar receives a percentage of 94% after the action, whereas on the initial ability test, Ar received a percentage of 26%. Rj received a percentage of 89%, up from 18% in his initial abilities. As a result, it can be said that the research aims to improve children's leek planting abilities using the project-based learning method, which can produce satisfactory results.